The Model Development of Teacher Competence Management Based on the Professional Learning Community (PLC) Approach at Wat Tha Kham School, Chiang Mai Province - Phisetchaturong , Aekkapong (MCU Haripunchai Review, 2026)
This research aimed to enhance teacher competency management in integrating digital technology into classroom teaching at Wat Tha Kham School, Chiang Mai, through the Professional Learning Community (PLC) approach. The study employed a Participatory Action Research (PAR) methodology over a 12-month period with five teachers. The research was conducted in two action cycles, each consisting of planning, implementation, observation, and reflection to support continuous learning and model development. The results showed that: 1) While teachers possessed basic digital skills, they lacked systematic support for professional development, collaboration, and school-level management. 2)In response, a comprehensive competency management model was developed comprising three core components: Input: Involves supportive leadership, access to technological resources, teacher readiness, and school context. Process: Guided by PLC principles and PAR cycles, with five steps: Co-planning to identify needs and goals, Technology enhancement workshops to build digital skills, Collaborative lesson planning (Lesson Study) to co-develop effective instructional strategies, Peer observation and feedback to improve teaching practices, Reflective dialogue to consolidate learning and promote continuous improvement. Output: Demonstrated increased teacher competency in three domains—knowledge, practical skills, and attitudes—with a focus on integrating digital tools meaningfully into lessons. 3)Implementation of the model resulted in notable behavioral changes. Teachers became more engaged, confident, and innovative in using digital media. Students were more motivated and actively participated in learning activities supported by tools like interactive games, videos, and surveys. The school, in turn, adopted a more structured approach to teacher development based on the model. 4) Evaluation showed significant improvements in teachers’ digital literacy, ability to design active learning environments, and use of technology for assessment. Satisfaction levels among teachers were high, emphasizing the model’s clarity, practicality, collaborative focus, and relevance to subject content—making it a sustainable framework for ongoing teacher professional development.